A survey on the aflatoxin M1 occurrence in raw milk and dairy products from water buffalo in South China. (November 2019) - Guo, Ling; Wang, Yanyan; Fei, Peng; Liu, Jianxin; Ren, Daxi
Abstract: The objective of this study was to investigate the levels of aflatoxin M1 (AFM1) concentration in raw milk and dairy products from water buffalo in south China. 136 raw milk and 86 dairy products samples were collected randomly from buffalo dairy pastures and supermarket in Guangxi, Guizhou, Yunnan and Guangdong province of south China during winter season. AFM1 levels were determined using the enzyme linked immunosorbent assay (ELISA) method and verified by high performance liquid chromatography (HPLC). AFM1 was detected in 85 (62.5%) of raw buffalo milk samples, and the content ranged between 4 and 243 ng/kg, among them, 8 (5.9%) samples were over the European Regulation (50 ng/kg). For the dairy products, AFM1 was found in 64 (74.4%) samples, and the content ranged between 4 and 235 ng/kg. AFM1 occurrence (100%) and content (43.1 ng/kg) in cheese was significantly higher than that in high temperature short time (HTST) milk, ultra heat treated (UHT) milk and yogurt. None of the raw milk and dairy products of AFM1 content was over the China standard (500 ng/kg). Therefore, AFM1 contamination in buffalo raw milk and dairy products was not represented a serious public health problem in south China. Highlights: The Occurrence and level of AFM1 in raw buffalo milk and buffalo milk products from southern China was investigated. AFM1 occurrence in raw buffalo milk is high and content is under Chinese standard. AFM1 occurrence in buffalo dairy products is high and AFM1 content is under EU limit.